Switch : how to change things when change is hard - Heath, Chip; Heath, Dan, 1973- (New York : Broadway Books, 2010)
In a compelling, story-driven narrative, the Heaths bring together decades of counterintuitive research in psychology, sociology, and other fields to shed new light on how we can effect transformative change. "Switch "shows that successful changes follow a pattern, a pattern you can use to make the changes that matter to you, whether your interest is in changing the world or changing your waistline
Three surprises about change -- Find the bright spots -- Script the critical moves -- Point to the destination -- Find the feeling -- Shrink the change -- Grow your people -- Tweak the environment -- Build habits -- Rally the herd -- Keep the switch going
Includes index
Keywords: Change (Psychology)